How Short Video Marketing on Xiaohongshu Empowers Brand Growth in the New Media Environment: A Case Study of Perfect Diary Cosmetics Analyzing Content Marketing and User Word-of-Mouth Effects - Wu, Yuran (International Journal of Social Sciences and Public Administration, 2024)
With the new media's rapid development, short video platforms have emerged as new brand marketing arenas. XiaoHongshu, a community platform combining shopping guides and lifestyle sharing, has garnered attention from brands for its unique user base and high engagement.This study chooses the Perfect Diary of cosmetics brand as a case to analyze how XiaoHongshu short video marketing promotes brand development, especially focusing on the actual effect of content marketing strategy and user feedback. The findings demonstrate that the Perfect Journal successfully engaged and engaged a large number of users through careful content design and effective collaboration with key opinion leaders. Statistics reveal that the brand's notes in the Little Red Book are displayed more than 100,000 times per month on average, and the number of views of a single video can reach up to 3 million times, which greatly enhances brand awareness and market influence. Additionally, by analyzing user comments and interaction data, this paper reveals the crucial role of positive reviews in promoting sales conversion, as well as how the brand effectively handles negative feedback to maintain a good brand image. In summary, this study demonstrates that in the new media environment, through precise content marketing and active user engagement, Perfect Diary has effectively leveraged the Xiaohongshu platform to enhance brand value and increase market share.